The Influence of Cost Leadership Strategy, Difference and Focus on the Performance of the Company at PT. Pwi - Ina Restiana (Jurnal Ekonomi, 2022)
The purpose of this study is to determine the effect of cost leadership strategy, differentiation strategy and focus strategy on company performance. The case study in this study was taken from PT. PWI, which is a manufacturing company engaged in the production of shoes and footwear. The population taken in this study, namely the employees of PT. PWI with a sample of 96 respondents who work within the scope of PT. PWI. The dependent variable (Y) in this study is company performance, while the independent variable (X) includes: Cost advantage strategy (X1), Differentiation Strategy (X2) and Focus Strategy (X3). Data analysis method using path analysis with IBM SPSS statistics 16 program which is fully carried out by the author and also related parties. The results of this study indicate that the cost advantage strategy, differentiation strategy and focus strategy have a positive and significant impact on company performance. The differentiation strategy is the most influential strategy compared to the other two strategies.